Datification of the wisdom of the crowd: A comparative analysis of innovation strategies in four European crowdfunding platforms - Foá, C. (Observatorio (OBS*), 2024)
Crowdfunding is a business model where diverse stakeholders operate in a context considered an example of innovation in value co-creation. Based on literature about service ecosystems and value co-creation this study adopts the platformization of society as critical theoretical approach and analytical framework to study the relations between human and technological agents within four crowdfunding ecosystems in Europe. Conceiving Crowdfunding Service Providers (CSPs) as specialized organizations, regulated to operate multi-sided markets and to serve roles as ecosystems’ coordinators, we aim to identify the innovation strategies adopted by CSPs platforms from Italy, France, Spain and Portugal to support their core functions related to governance mechanisms, business models and infrastructural components. To understand the motives for innovation implementation and to compare the competitive adaptation from an ecosystemic perspective, we triangulate qualitative data from multiple sources to explain how and why these strategic choices affect the dynamics of value co-creation. The multiple cases-study systematizes and discusses similarities and differences, particularly as concerns the capacity of CFPs to orchestrate their governance and ICT components to innovate and take advantage of algorithms and AI implementation, collecting more data and money from user interactions. Conclusions highlight the non-neutrality of CSPs, which act as data analysts and translators, adopting more preventive, proactive or reactive strategies of usage and redistribution of the value, created, acquired and aggregated through data. Each CSP can be characterized by its infrastructure and data management approach, metaphorically being more eco-centred or ego-centred.